Teacher Strategies in Learning during the Covid-19 Pandemic at Madrasah Ibdidaiyah Negeri (MIN) 2 Central Aceh - Suwarno Suwarno; Muhammad Almi Hidayat; Siti Zumrotul Nikmah; Rahmah Nurfitriani; Ramadan Ramadan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Coronavirus (covid-19) has changed the life of various sectors, including the education sector. Since March 2020 education in Indonesia has implemented Distance Learning (PJJ), starting from Kindergarten (TK) to Higher Education levels. Distance learning which is carried out online and offline has caused many problems, because it is a new learning in Indonesia, especially in Indonesia. low level such as Elementary School/Madrasah Ibdidaiyah. One of them is how to convey lessons during the Covid-19 period. In this study, the authors wanted to know the strategies of MIN 2 Aceh Tengah teachers in learning during the covid-19 period. The research approach used in this study is a qualitative research type. The research location is in MIN 2 Central Aceh from November 16, 2020, to January 8, 2021. Data collection is carried out using observation and interviews, the observations of the researchers are carried out by observing the teacher's activities in learning, while the researcher interviews are conducted to obtain comprehensive information about the teacher's strategies in motivating children's learning during the covid-19 period. Data analysis techniques include interview transcripts, data reduction, analysis, data interpretation, and triangulation. From the results of data analysis, conclusions can then be drawn. The results showed that in the low class the strategy used by grade 1 and grade 2 teachers at MIN 2 Aceh Tengah was by making small classes, and learning was carried out by home visits, while grades 3 to 6 were carried out face-to-face in a rotating system. The strategies used by the teacher include direct, expository, cooperative, and contextual learning.